How to Sustain Export Dynamism by Reducing Duality in the Dominican Republic - World Bank (Washington, DC, 2015)
This report analyzes export competitiveness in the Dominican Republic drawing from the Trade Competitiveness Diagnostic methodology (Farole and Reis, 2012). Dominican exports fare well in terms of performance, sophistication, and survival in Special Economic Zones. Three main challenges are identified: 1) quality issues and rejection of agro exports in the US border; 2) the role of Special Economic Zones in the new decade and the lack of backward linkages; and 3) excessive concentration in terms of markets that is not addressed by a fragmented institutional setup.